Light at night disrupts nocturnal rest and elevates glucocorticoids at cool color temperatures. Issue 8 (15th May 2018) - Alaasam, Valentina J.; Duncan, Richard; Casagrande, Stefania; Davies, Scott; Sidher, Abhijaat; Seymoure, Brett; Shen, Yantao; Zhang, Yong; Ouyang, Jenny Q.
Abstract: Nighttime light pollution is quickly becoming a pervasive, global concern. Since the invention and proliferation of light‐emitting diodes (LED), it has become common for consumers to select from a range of color temperatures of light with varying spectra. Yet, the biological impacts of these different spectra on organisms remain unclear. We tested if nighttime illumination of LEDs, at two commercially available color temperatures (3000 and 5000 K) and at ecologically relevant illumination levels affected body condition, food intake, locomotor activity, and glucocorticoid levels in zebra finches (Taeniopygia guttata) . We found that individuals exposed to 5000 K light had higher rates of nighttime activity (peaking after 1 week of treatment) compared to 3000 K light and controls (no nighttime light). Birds in the 5000 K treatment group also had increased corticosterone levels from pretreatment levels compared to 3000 K and control groups but no changes in body condition or food intake. Individuals that were active during the night did not consequently decrease daytime activity. This study adds to the growing evidence that the spectrum of artificial light at night is important, and we advocate the use of nighttime lighting with warmer color temperatures of 3000 K instead of 5000 K to decrease energetic costs for avian taxa. GRAPHICAL ABSTRACT: Exposure to dim (0.3 lux) 5000K LED light at night caused an increase in nocturnal activity (peaking after 7 days) and baseline corticosterone (measured after 3 weeks) in captive zebra finches, relative to 3000K light which had no effect .